Legal Protection for Owners of Inherited Property in Marriage Agreements Based on Law No. 16 of 2019 About Marriage - Lusia Nova Hutasoit; Roida Nababan; Meli Hertati Gultom (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the law of inherited property during marriage as well as to identify the type of legal protection provided to the owner of inherited property through a marriage agreement. This study uses a normative juridical approach that emphasizes analytical and legislative approaches. Data was collected through research on primary, secondary, and tertiary legal materials. The findings of the study show that the marriage agreement provides legal protection for the owner of the defalut in a repressive and preventive manner. Prevention of a marriage agreement can reduce the mixing of assets and protect the ownership of inherited property, and repressively a marriage agreement can provide legal certainty in handling the ownership of inherited property. This study concludes that the marriage agreement is an effective legal instrument to protect the rights of the owner of the property, as well as understand the importance of the marriage agreement as a legal protection in a preventive marriage.